Chemosensory Alterations and Impact on Quality of Life in Persistent Alcohol Drinkers. (7th October 2022) - Agarwal, Khushbu; Luk, Jeremy W; Manza, Peter; McDuffie, Christian; To, Leann; Jaime-Lara, Rosario B; Stangl, Bethany L; Schwandt, Melanie L; Momenan, Reza; Goldman, David; Diazgranados, Nancy; Ramchandani, Vijay A; et al.
Abstract: Background: Heavy alcohol consumption-associated chemosensory dysfunction is understudied, and early detection can help predict disease-associated comorbidities, especially those related to four quality of life (QOL) domains (physical, psychological, social and environment). We examined self-reports of chemosensory ability of individuals with different alcohol drinking behaviors and their association with changes in QOL domains. Methods: Participants ( n = 466) were recruited between June 2020 and September 2021 into the NIAAA COVID-19 Pandemic Impact on Alcohol study. Group-based trajectory modeling was used to categorize participants without any known COVID-19 infection into three groups (non-drinkers, moderate drinkers and heavy drinkers) based on their Alcohol Use Disorders Identification Test consumption scores at four different time points (at enrollment, week 4, week 8 and week 12). Linear mixed models were used to examine chemosensory differences between these groups. The associations between chemosensory abilities and QOL were determined in each group. Results: We observed significant impairment in self-reported smell ability of heavy drinking individuals compared to non-drinkers. In contrast, taste ability showed marginal impairment between these groups. There were no significant differences in smell and taste abilities between the moderate and non-drinking groups. Heavy drinkers' impairment in smell and taste abilities was significantly associated with deterioration in their physical, psychological, social and environmental QOL. Conclusion: Persistent heavy drinking was associated with lower chemosensory ability. Heavy drinkers' reduced smell and taste function and association with poorer QOL indicate that early assessment of chemosensory changes may be crucial in identifying poorer well-being outcomes in heavy drinkers at risk for alcohol use disorder. Abstract : Short Summary: Persistent heavy alcohol drinking leads to smell dysfunction as evident from our longitudinal four time point study. Group-Based Trajectory Modeling on the AUDIT consumption scores of four hundred and forty participants identified heavy-, moderate-, and non-drinking groups. A significant self-reported smell impairment was seen in heavy drinkers (vs. non-drinkers), which associated positively with the deterioration in their overall quality of life.